(untitled) (Architecture Image Studies, 2025)
This study examines the frictional behavior of polyethylene (PE) and polyamide (PA) materials used in friction pendulum systems (FPS) for bridge bearings under various contact pressures (20, 40 and 60 MPa) and sliding velocities (1–200 ㎜/s). The friction coefficients were measured experimentally, and a logarithmic regression model was applied to assess velocity sensitivity. Based on the measured coefficients, FPS designs were conducted to evaluate effective stiffness, energy dissipation capacity, and equivalent damping ratio under identical design conditions. Results indicate that PA consistently exhibited higher friction coefficients, greater energy dissipation, and superior damping performance compared to PE. These findings provide practical insights into selecting optimal friction materials for seismic isolation bearings, enabling enhanced damping capacity and compact bearing designs.